PERAN PUBLIC RELATIONS DALAM MENINGKATKAN CITRA HOTEL SAHID MELALUI EVENT YOGA - Asti Haningtyas (Jurnal Riset Komunikasi, 2018)
Hotel industry is currently booming and Grand Sahid Jaya Hotel - Jakarta, which has been established since 1974, is facing tough competition with the arrival of hotels offering a variety of themes and more affordable prices. The image of Grand Sahid Jaya Hotel - Jakarta has been declining and public relations plays an important role in rebuilding, maintaining, and improving the hotel’s image. This research was done to understand the role of public relations in improving the image of Grand Sahid Jaya Hotel - Jakarta through the Sunrise Yoga from the Skyline event using qualitative data for the research method. This study also uses the role of public relations elements by Ruslan. The research results shows that public relation plays an important role and has fulfilled its theoretical role that was used to improve the image of Grand Sahid Jaya - Jakarta.